Studies on monocytes in inflammatory bowel disease: factors influencing monocyte lysosomal enzyme activity. - Mee, A; Nuttall, L; Potter, B; Jewell, D (1980)
The effect of endotoxin and immune complexes on monocyte lysosomal enzyme activity has been studied in patients with Crohn's disease and ulcerative colitis. Immune complexes made at equivalence or in antigen excess caused a rapid fall in intracellular activity of the enzyme N'acetyl-beta-D-glucosaminidase which was significantly greater than that seen when cells were incubated with medium alone. Endotoxin had no effect on intracellular enzyme activity but there was a significant elevation of activity in the supernatants. Cells from patients with inflammatory bowel disease were no different to cells from healthy control subjects in their response to either endotoxin or immune complexes.